Real‐world Omalizumab and Mepolizumab treated difficult asthma phenotypes and their clinical outcomes. Issue 8 (6th May 2021) - Fong, Wei Chern Gavin; Azim, Adnan; Knight, Deborah; Mistry, Heena; Freeman, Anna; Felongco, Mae; Kyyaly, Aref; Harvey, Matthew; Dennison, Patrick; Zhang, Hongmei; Howarth, Peter; Arshad, Syed Hasan; et al.
Abstract: Background: Omalizumab and Mepolizumab are biologic drugs with proven efficacy in clinical trials. However, a better understanding of their real‐world effectiveness in severe asthma management is needed. Objectives: To better understand the real‐world effectiveness of Omalizumab and Mepolizumab, elucidate the clinical phenotypes of patients treated with these drugs, identify baseline characteristics associated with biologic response and assess the spectrum of responses to these medications. Methods: Using real‐world clinical data, we retrospectively phenotyped biologic naïve patients from the Wessex AsThma CoHort of difficult asthma ( N  = 478) commenced on Omalizumab ( N  = 105) or Mepolizumab ( N  = 62) compared to severe asthma patients not receiving biologics (SNB, N  = 178). We also assessed multiple clinical endpoints and identified features associated with response. Results: Compared to SNB, Omalizumab patients were younger, diagnosed with asthma earlier, and more likely to have rhinitis. Conversely, compared to SNB, Mepolizumab patients were predominantly older males, diagnosed with asthma later, and more likely to have nasal polyposis but less dysfunctional breathing. Both treatments reduced exacerbations, Acute Healthcare Encounters [AHE] (emergency department or hospital admissions), maintenance oral corticosteroid dose, and improved Asthma Control Questionnaire 6 (ACQ6) scores. Omalizumab response was independently associated with more baseline exacerbations ( p  = .024) but fewer AHE ( p  = .050) and absence of anxiety ( p  = .008). Lower baseline ACQ6 was independently associated with Mepolizumab response ( p  = .007). A composite group of non‐responders demonstrated significantly more psychopathologies and worse baseline subjective disease compared to responder groups. Conclusions and Clinical Relevance: In a difficult asthma cohort, Omalizumab and Mepolizumab were used in distinct clinical phenotypes but were both multidimensionally efficacious. Certain baseline clinical characteristics were associated with poorer biologic responses, such as psychological co‐morbidity, which may assist clinicians in biologic selection. These characteristics also emphasize the need for comprehensive approaches to support these patients.